2015
DOI: 10.1016/j.watres.2015.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight inactivation of fecal indicator bacteria in open-water unit process treatment wetlands: Modeling endogenous and exogenous inactivation rates

Abstract: A pilot-scale open-water unit process wetland was monitored for one year and found to be effective in enhancing sunlight inactivation of fecal indicator bacteria (FIB). The removal of Escherichia coli and enterococci in the open-water wetland receiving non-disinfected secondary municipal wastewater reached 3 logs and 2 logs in summer time, respectively. Pigmented enterococci were shown to be significantly more resistant to sunlight inactivation than non-pigmented enterococci. A model was developed to predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 37 publications
(47 reference statements)
2
94
0
1
Order By: Relevance
“…Figure 9b shows free water surface flow wetlands are expected to achieve a wide range of removal of bacteria and viruses that can range from less than 1 log 10 reduction to up to 2 or 3 log 10 reduction. This supports the conclusions of others (e.g., Nguyen et al, 2015;Silverman et al, 2015) that sunlight inactivation is very important for virus and bacteria reductions and this mechanism may be limited in a free water surface flow constructed wetland that contains emergent plants because of shading of the water by the vegetation. The observations in Figure 9a and 9b are also supported by who showed that horizontal subsurface flow constructed wetlands typically have a better capacity to remove pathogens than a planted free water surface flow constructed wetlands.…”
Section: Summary Of Data On Pathogen Removal In Constructed Wetland Ssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 9b shows free water surface flow wetlands are expected to achieve a wide range of removal of bacteria and viruses that can range from less than 1 log 10 reduction to up to 2 or 3 log 10 reduction. This supports the conclusions of others (e.g., Nguyen et al, 2015;Silverman et al, 2015) that sunlight inactivation is very important for virus and bacteria reductions and this mechanism may be limited in a free water surface flow constructed wetland that contains emergent plants because of shading of the water by the vegetation. The observations in Figure 9a and 9b are also supported by who showed that horizontal subsurface flow constructed wetlands typically have a better capacity to remove pathogens than a planted free water surface flow constructed wetlands.…”
Section: Summary Of Data On Pathogen Removal In Constructed Wetland Ssupporting
confidence: 90%
“…In addition, reactions mediated by exogenous photosensitizers can induce lesions in the transport chains in water that contains dissolved organic matter (Muela et al, 2002). However, it is reported that though exogenous photosensitizers played a role in inactivation rates of E. faecalis, they did not play an important role in the inactivation of E. coli in similar experiments (Kadir and Nelson, 2014;Nguyen et al 2015).…”
Section: Sunlight and Water Claritymentioning
confidence: 94%
“…A number of studies have therefore investigated bacterial photoinactivation in the context of environmental water quality (1)(2)(3)(4)(5)(6)(7), with further studies also focusing on photoinactivation in drinking water treatment (8)(9)(10)(11), photodynamic therapy (12)(13)(14)(15), and wastewater treatment (16)(17)(18)(19)(20). Bacteria can be inactivated by sunlight by direct and indirect mechanisms.…”
mentioning
confidence: 99%
“…Previous studies have identified factors and characteristics associated with increased photoinduced damage of FIB. For example, higher concentrations of dissolved oxygen lead to increased photoinactivation of fecal coliforms and Enterococcus faecalis (6,17), and the presence of carotenoid pigments in certain enterococci tends to decrease their susceptibility to photoinactivation (4,18). However, most previous research has focused on loss of culturability as the sole metric of photoinactivation, with a limited number of studies also addressing the effects of sunlight exposure on membrane integrity, cell metabolism, protein content, and gene expression in FIB (6)(7)(8)29).…”
mentioning
confidence: 99%
See 1 more Smart Citation